Air-release, air/vacuum, and combination air valves. (American Water Works Association, 2001)
Annotation "Operators, technicians, and engineers will find the information in this manual useful for gaining a basic understanding of the use and application of air valves. A valuable guide for selecting, sizing, locating, and installing air valves in water applications, M51 provides information on air valve types listed in AWWA Standard C512, latest edition, including the following: air-release valve; air/vacuum valve; and combination air valve."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Keywords: Water-pipes -- Valves.; Air valves.; elektronické knihy; electronic books